2020
DOI: 10.3390/microorganisms8050757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Manganese on Intestinal Barrier and Inflammatory Response in Broilers Challenged with Salmonella Typhimurium

Abstract: Growing concern for public health and food safety has prompted a special interest in developing nutritional strategies for removing waterborne and foodborne pathogens, including Salmonella. Strong links between manganese (Mn) and intestinal barrier or immune function hint that dietary Mn supplementation is likely to be a promising approach to limit the loads of pathogens in broilers. Here, we provide evidence that Salmonella Typhimurium (S. Typhimurium, 4 × 108 CFUs) challenge-induced intestinal injury along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…The higher Mn group also had higher percentages of CD4+ and CD8+ T-cells in peripheral blood and modulated cytokine gene expression in spleen, caecal tonsils, and bursa of Fabricius. In another Salmonella Typhimurium broiler chicken challenge study, greater duodenal villus height, increased jejunal Lactobacillus and Bifidobacterium and decreased Salmonella and E. coli , higher tight junction gene expression and reduced gut permeability, reduced numbers of Salmonella in both caecal content and spleen, greater splenic proinflammatory gene expression and mitochondrial MnSOD activity, and activation of acute-phase response, T helper type 1, and dendritic cell maturation pathways were associated with higher Mn supplementation (basal diet + 100 mg Mn/kg) in comparison to a Mn adequate (basal diet + 40 mg Mn/kg) and/or deficient (basal diet + 0 mg Mn/kg) diets [ 64 ]. Interestingly, there were also differences in specific broiler chicken peripheral blood T and innate cell proportions following Salmonella Enteritidis vaccination between birds fed diets providing 80 mg Mn/kg via MnSO 4 supplementation alone or a 50:50 mix of MnSO 4 and Mn amino acid complex [ 65 ], again indicating the importance of Mn source(s) for the biological response.…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…The higher Mn group also had higher percentages of CD4+ and CD8+ T-cells in peripheral blood and modulated cytokine gene expression in spleen, caecal tonsils, and bursa of Fabricius. In another Salmonella Typhimurium broiler chicken challenge study, greater duodenal villus height, increased jejunal Lactobacillus and Bifidobacterium and decreased Salmonella and E. coli , higher tight junction gene expression and reduced gut permeability, reduced numbers of Salmonella in both caecal content and spleen, greater splenic proinflammatory gene expression and mitochondrial MnSOD activity, and activation of acute-phase response, T helper type 1, and dendritic cell maturation pathways were associated with higher Mn supplementation (basal diet + 100 mg Mn/kg) in comparison to a Mn adequate (basal diet + 40 mg Mn/kg) and/or deficient (basal diet + 0 mg Mn/kg) diets [ 64 ]. Interestingly, there were also differences in specific broiler chicken peripheral blood T and innate cell proportions following Salmonella Enteritidis vaccination between birds fed diets providing 80 mg Mn/kg via MnSO 4 supplementation alone or a 50:50 mix of MnSO 4 and Mn amino acid complex [ 65 ], again indicating the importance of Mn source(s) for the biological response.…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…The most prevalent Salmonella serovars are including S. Typhimurium, S. Enteritidis, S . Pullorum and S. Gallinarum, among them, S. Typhimurium and S. Enteritidis have been described as worldwide spread [ 1 , 2 , 3 ]. Some of these prevalent serovars could lead to serious zoonotic diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tight junction proteins (e.g., claudin-1, occludin, and ZO-1) are crucial molecules for the maintenance of intestinal epithelial barrier integrity ( Pei et al, 2019 ; Konieczka et al, 2020 ). Previous studies reported that S. Typhimurium could disrupt the tight junction structure in broilers and T84 intestinal epithelial cells ( Zhang H. et al, 2020 ). Our results showed that the expression levels of tight junction proteins were significantly downregulated with S. Typhimurium challenge relative to the CON group, which was consistent with previous reports ( Zhang H. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence suggests that Salmonella challenge decreases productivity and increases the Salmonella colonization of organs ( Symonds et al, 2012 ; Zhang H. et al, 2020 ). In our study, compared with the uninfected control (CON) group, the body weight of chickens infected with Salmonella was significantly decreased, and the S. Typhimurium load was dramatically increased in the feces and organs, which was consistent with a previous report ( Zhang H. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation